Membangun Literasi Politik Melalui Pendidikan Untuk Pemilu yang Bermartabat - Fauzan Ali Rasyid (SIYASI: Jurnal Trias Politica, 2023)
Abstract; The weakness and strength of political literacy greatly influence the process and outcomes of elections. Therefore, enhancing political literacy is an obligation that needs to be improved through political education. Higher education institutions have a responsibility in enhancing political literacy to achieve dignified elections. The findings of this research indicate that higher education institutions play a central role in improving political literacy and building reputable elections, despite facing several challenges such as limited curriculum, limited resources, gender imbalances, technological challenges, and challenges related to politics and freedom of expression.